2020
DOI: 10.1186/s13063-020-04584-9
|View full text |Cite
|
Sign up to set email alerts
|

ACCORD: A Multicentre, Seamless, Phase 2 Adaptive Randomisation Platform Study to Assess the Efficacy and Safety of Multiple Candidate Agents for the Treatment of COVID-19 in Hospitalised Patients: A structured summary of a study protocol for a randomised controlled trial

Abstract: Objectives: Stage 1: To evaluate the safety and efficacy of candidate agents as add-on therapies to standard of care (SoC) in patients hospitalised with COVID-19 in a screening stage. Stage 2: To confirm the efficacy of candidate agents selected on the basis of evidence from Stage 1 in patients hospitalised with COVID-19 in an expansion stage. Trial design: ACCORD is a seamless, Phase 2, adaptive, randomised controlled platform study, designed to rapidly test candidate agents in the treatment of COVID-19. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 0 publications
2
70
0
2
Order By: Relevance
“…It is anticipated that a MASP inhibitor such as Narsoplimab will not exert a massive therapeutic effect on the EM pathogenesis since no evidence is available so far that is suggestive of a key involvement of the complement lectin pathway in the EM lesion formation. Various prospective anti-complement inhibitors studied so far are listed in Table 1 and Figure 4 ( 128 , 141 176 ).…”
Section: Possibility Of Anti-complement Immunotherapy In Endometriosimentioning
confidence: 99%
“…It is anticipated that a MASP inhibitor such as Narsoplimab will not exert a massive therapeutic effect on the EM pathogenesis since no evidence is available so far that is suggestive of a key involvement of the complement lectin pathway in the EM lesion formation. Various prospective anti-complement inhibitors studied so far are listed in Table 1 and Figure 4 ( 128 , 141 176 ).…”
Section: Possibility Of Anti-complement Immunotherapy In Endometriosimentioning
confidence: 99%
“…Positive results in Phase 1b studies in renal indications are announced on their webpage, however, no further details are provided ( 216 ). On 11 May 2020, a prospective clinical study of zilucoplan in COVID-19 was initiated ( 217 ).…”
Section: Terminal Complement Pathway Inhibitors In Other Indicationsmentioning
confidence: 99%
“…A similar effect has been suggested in SARS-CoV ( 228 , 234 ) and increased C5a levels have been found in COVID-19 patients ( 18 ). Consequently, several C5, C5a, and C5aR1 inhibitors are currently undergoing clinical studies in COVID-19, such as eculizumab, which has already showed preliminary efficacy ( 236 ), ravulizumab ( 237 ), zilucoplan ( 217 ), IFX-1 ( 203 ), and avdoralimab ( 224 ).…”
Section: Terminal Complement Pathway Inhibitors In Other Indicationsmentioning
confidence: 99%
“…Aiming at reducing the hyper inflammation found in the lungs of SARS-CoV-2-infected patients, different clinical studies are currently investigating the activities of mAbs anti-JAK, anti-GM-CSF, anti-GM-CSF receptor, anti-M-CSF receptor, anti-CD14, anti-IFNg, anti-VEGF, anti-BKT, anti-CCR5, anti-IL-6, anti-IL-6 receptor, anti-TNFa, anti-IL1b, anti-IL1b receptor, and complement C5 inhibitor (220,251,252). Similarly, ongoing clinical trials have sought to reverse the hyper-thrombotic state found in critically ill patients by using anti-P-selectin, anti-CTGF, and factor XIIa antagonist mAbs (253,254).…”
Section: Antibody-based Therapymentioning
confidence: 99%